2021
DOI: 10.1002/anie.202101864
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis Targeting Chimera (PROTAC) for Macrophage Migration Inhibitory Factor (MIF) Has Anti‐Proliferative Activity in Lung Cancer Cells

Abstract: Macrophage migration inhibitory factor (MIF) is involved in protein-protein interactions that play key roles in inflammation and cancer.C urrent strategies to develop small molecule modulators of MIF functions are mainly restricted to the MIF tautomerase active site.H ere,w eu se this site to develop proteolysis targeting chimera (PROTAC)i no rder to eliminate MIF from its protein-protein interaction network. We report the first potent MIF-directed PROTAC, denoted MD13, which induced almost complete MIF degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“… 27 , 28 Moreover, we developed a potent MIF-targeted proteolysis targeting chimera (PROTAC) to remove the MIF protein from its interaction network, which further expanded the toolbox to study MIF functions. 29 However, little is known about the effect of MIF2 inhibitors on cancer development due to a lack of potent MIF2 inhibitors and other effective molecular tools. 4-Iodo-6-phenylpyrimidine (4-IPP) is the firstly discovered MIF2 inhibitor, which covalently binds to proline-1 of MIF2 to interfere with its tautomerase enzyme activity and its biological function.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 Moreover, we developed a potent MIF-targeted proteolysis targeting chimera (PROTAC) to remove the MIF protein from its interaction network, which further expanded the toolbox to study MIF functions. 29 However, little is known about the effect of MIF2 inhibitors on cancer development due to a lack of potent MIF2 inhibitors and other effective molecular tools. 4-Iodo-6-phenylpyrimidine (4-IPP) is the firstly discovered MIF2 inhibitor, which covalently binds to proline-1 of MIF2 to interfere with its tautomerase enzyme activity and its biological function.…”
Section: Introductionmentioning
confidence: 99%
“…MIF is a cytokine closely associated with cancer and functions as a promoter in inflammation, and inhibition of MIF can suppress cancer cell proliferation [ 67 ]. Also, a study confirmed that proteolysis targeting chimera designed based on MIF tautomerase active site exhibited excellent anti-proliferative activity in lung cancer cells [ 68 ]. Moreover, exposure to SARS-CoV-2 spike protein combined with hypoxia enhanced MIF production [ 69 ].…”
Section: Discussionmentioning
confidence: 97%
“…c) Western blot assay of GPX4 level in HT‐1080 cells treated with different concentrations of ML162 and pomalidomide. d) Rescue from dGPX4‐mediated GPX4 degradation upon co‐treatment with CRBN‐inhibitor, pomalidomide, [16] and MG‐132. HT‐1080 cells were pre‐treated with indicated compounds for 12 h.…”
Section: Resultsmentioning
confidence: 99%